Carbon dioxide gas endoscopy of the deep gluteal space. Issue 4 (1st October 2020) - Martin, Hal David; Hatem, Munif; Gómez-Hoyos, Juan; Pérez-Carro, Luis; Khoury, Anthony N.
Abstract: The treatment of hip and pelvic pain associated with abnormalities of the deep gluteal space has evolved and increasingly involves endoscopic techniques with a saline expansion medium. This investigation presents a surgical technique utilizing carbon dioxide as the insufflation medium for deep gluteal space endoscopy in 17 cadaveric hips. This technique was successful in 94% (16/17) of the hips, allowing for visualization of the sciatic nerve, posterior femoral cutaneous nerve, pudendal nerve, branch of the inferior gluteal artery crossing the sciatic nerve, piriformis muscle, hamstring tendon origin, and lesser trochanter. Our experience suggests that gas expansion presents several advantages over fluid expansion.